Environmental and health studies of farm workers in Swedish swine confinement buildings. Issue 1 (January 1989) - Donham, K; Haglind, P; Peterson, Y; Rylander, R; Belin, L
Abstract : The relation between the health of workers and the environment in swine confinement buildings was investigated in a study of 57 workers on 30 swine farms in southern Sweden and 55 matched controls. Swine workers reported significantly higher frequencies of respiratory symptoms, more frequent colds and absence due to chest illness, and a history of pneumonia. The increased frequency of symptoms of respiratory disease was related to the number of years and percent of the day spent working with swine. Symptoms were also associated with respirable dust, total dust, endotoxin in total dust, and number of microbes in the air of the work environment. In a multiple regression analysis of the relation between 16 different environmental parameters to work period shifts of five pulmonary function parameters, endotoxin was found to be significantly related to the FEV1 in a dose dependent way.